“Creación de un centro de acopio de gas de uso doméstico sector el Tambo, parroquia San Buenaventura”. - Arcos Arcos, Mayra del Carmen (2022)
The general objective of this work is the creation of a collection center for the commercialization of gas for domestic use in the dairy sector of the San Buenaventura parish in the city of Latacunga, based on the CANVAS model, taking as an object of study the entrepreneurship, in such a way as to answer the question: How to improve the supply of 15 kg LPG cylinders to families in the Tambo Parroquia San Buenaventura sector in the city of Latacunga? For this, a survey methodology was used that allowed to analyze the needs of the inhabitants, such as the use of 1 monthly gas cylinder per family made up of 4 people, in the administrative study the fundamental areas and the people who are necessary to develop the activities were identified, in the study of market it was possible to define the demand, with the technical study the installed capacity and the requirements related to infrastructure were established There are teams, while the financial study shows very important indicators such as IRR of 31.94% and a NPV of $42,033.49, the studies allowed establishing the most important resources, knowing the most appropriate distribution channels, applying an analysis of the internal and external environment In order to know the advantages and disadvantages that the company has in the market, the consumer's perspective is analyzed within the proposal, as well as the acceptance for the existence of a gas collection center for domestic use within the parish of San Buenaventura in the sector. the Tambo, in the same way a technical study was carried out detailing the installed and used capacity of commercialization of the product according to the infrastructure and the human resource with which a quality service will be provided, the present study allows to determine that the The project is feasible and profitable and above all it will allow to satisfy the needs of such an important sector of Latacunga.